Advancing medical image security: a hybrid DNA-AES based cryptosystem - Khan, Chisthia; Ayesha, Tasfia; Fahomida, Maiesha; Alam, Samiha Jubaida; Hossain, Nushraq Nawer (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.